KINERJA APARATUR SIPIL NEGARA PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Beril Kolip Arahman; Syahruddin Hattab; Sitti Chaeriah Ahsan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to find out how the State Civil Apparatus performs in the Protocol and Communication Section of the Regional Secretariat Leadership of Sigi Regency, Central Sulawesi Province. In this research, researchers used Moeheriono's theory (2012:162-163) which consists of the criteria of Responsiveness, Responsibility and Accountability. The research method used is a qualitative descriptive research type. Data collection was carried out using observation, documentation and interview methods. The determination and number of informants in this research were parties who were deemed to know in depth various matters relating to the research problem, totaling 5 (five) people. Meanwhile, data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions/verification. The results of this research show that the performance of the State Civil Apparatus in the Protocol and Communication Section of the Regional Secretariat Leadership of Sigi Regency, Central Sulawesi Province has not been running optimally, this is due to the failure to achieve the performance indicators used in this research, such as the aspect of responsiveness which has not been maximized due to resources. Humans in the scope of performance of the State Civil Apparatus in the Protocol and Communication Section of the Regional Secretariat Leadership of Sigi Regency, Central Sulawesi Province, which is still limited, especially in the placement of executive positions, is not in accordance with the competence of the employees in this agency in carrying out their duties. The responsibility aspect has not run optimally due to frequent delays in completing tasks because work is often postponed. The accountability aspect has gone well in implementing the ASN Core Values with AKHLAK but still needs to be socialized again, considering that these values are new things that need to be implemented. apply and serve as a guideline for carrying out duties by each ASN in providing services